Penerapan Electronic Government di Dinas Komunikasi dan Informatika Provinsi Kalimantan Timur - Dyah Rahayuning Perwitasari; Erwin Resmawan Erwin Resmawan; Hairunnisa Hairunnisa (Journal Social Politica, 2020)
Electronic Government is an important part of this modern era. This technological advancement is utilized in the scope of government in order to realize effective and efficient public services. This research includes a type of qualitative descriptive research with purposive sampling techniques. The result of this study are known that from all five indicators of the implementation of electronic government has been fulfilled. So the implementation of this electronic government can be said to have been implemented has not fully run its maximum. The implementation of electronic government in the Communication and Informatics Office of East Kalimantan Province has not fully run its maximum because it is largely influenced by the inadequate infrastructure of internet network in each region, so that more coordination and communication is done manually and does not apply electronic government.